2022
DOI: 10.1088/1741-2552/ac76e0
|View full text |Cite
|
Sign up to set email alerts
|

Brain–computer interface-based action observation combined with peripheral electrical stimulation enhances corticospinal excitability in healthy subjects and stroke patients

Abstract: Objective: Action observation (AO) combined with brain computer interface (BCI) technology enhances the cortical activation. Peripheral electrical stimulation (PES) is known to increase the corticospinal excitability, thereby activating brain plasticity. To maximize motor recovery, we assessed the effects of BCI-AO combined with PES on corticospinal plasticity. Approach: Seventeen patients with chronic hemiplegic stroke and 17 healthy subjects were recruited. The participants watched a video of repetitive gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…Our M1 intervention findings are in agreement with the proposed mechanism that BCI-FES usage involves Hebbian-like learning [9,[16][17][18]. In short, the repeated presynaptic cortical activation detected by the BCI system, which is closely followed by postsynaptic sensory nerve activation and movement-related reafference elicited using FES, could strengthen corticospinal projections after the intervention, as previously proposed [3,9,16,18]. The M1 area has direct corticospinal projections to the spinal motoneurons [14].…”
Section: Effectiveness Of Motor Cortical Activity For Bci-fes-induced...supporting
confidence: 90%
See 3 more Smart Citations
“…Our M1 intervention findings are in agreement with the proposed mechanism that BCI-FES usage involves Hebbian-like learning [9,[16][17][18]. In short, the repeated presynaptic cortical activation detected by the BCI system, which is closely followed by postsynaptic sensory nerve activation and movement-related reafference elicited using FES, could strengthen corticospinal projections after the intervention, as previously proposed [3,9,16,18]. The M1 area has direct corticospinal projections to the spinal motoneurons [14].…”
Section: Effectiveness Of Motor Cortical Activity For Bci-fes-induced...supporting
confidence: 90%
“…Non-invasive brain-computer interface (BCI)controlled functional electrical stimulation (FES) has been postulated to have the potential to contribute to the recovery of upper limb motor function after stroke [1][2][3][4][5][6] and incomplete spinal cord injury (SCI) [7,8]. The motor facilitation after the use of BCI-controlled FES has been reported to be associated with corticospinal [3] and cortical [1,2,5] excitability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study introduced the concept of attentional state-dependent PES during the AO paradigm using the BCI-SSVEPs protocol (Kim et al, 2022 ). The results indicated that the attentional state-dependent PES task was superior to AO alone or to a simple combination of AO and PES in facilitating corticospinal plasticity in both patients with stroke and in healthy individuals (Kim et al, 2022 ). Moreover, this paradigm is effective in enhancing sensorimotor cortical activation in the affected hemispheres of stroke patients (Lim et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%